2017
DOI: 10.1515/ijamh-2015-0041
|View full text |Cite
|
Sign up to set email alerts
|

Oral health impact, dental caries experience, and associated factors in 12–15-year-old school children in India

Abstract: Oral health had a significant effect on the quality of life of schoolchildren. The prevalence of dental caries was found to be high. Effective policies need to be drafted for oral health promotion in this age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 13 publications
3
25
0
1
Order By: Relevance
“…This is supported by our ndings which revealed, even after adjustment in the multivariate analysis, a highly signi cant association found between the lowest family income tertile and OHRQoL. Similar ndings have been reported in other studies among children in Brazil and India [26,35,36]. It is therefore important to assess socio economic conditions in general when dealing with OHRQoL, even among school children who are eligible for free hospital dental services in Sri Lanka.…”
Section: Discussionsupporting
confidence: 89%
“…This is supported by our ndings which revealed, even after adjustment in the multivariate analysis, a highly signi cant association found between the lowest family income tertile and OHRQoL. Similar ndings have been reported in other studies among children in Brazil and India [26,35,36]. It is therefore important to assess socio economic conditions in general when dealing with OHRQoL, even among school children who are eligible for free hospital dental services in Sri Lanka.…”
Section: Discussionsupporting
confidence: 89%
“…Sociodemographic characteristics, such as the child's sex (male/female), age (7, 8, 9, 10, 11, and 12 year olds), school grade during the study (1)(2)(3)(4)(5), residence area (living in a village belonging to Yasuj township was considered to be rural, and living in Yasuj city was considered to be urban), parents' education level (primary, high school, complete high school, and bachelor's or higher), and parents' professional situation (office worker, freelancer, and/or housewife) (employee/not employed), were collected using a structured questionnaire. Dental examination was performed at the schools for all selected children by two professionals and calibrated dentists (kappa � 85%) according to the World Health Organization (WHO) dental caries diagnosis guideline.…”
Section: Data Collection and Dental Examinationmentioning
confidence: 99%
“…Dental caries is the most prevalent disease of the oral health in school-aged children around the world [1][2][3][4][5]. Dental caries leads to tooth pain, discomfort, eating impairment, loss of tooth, and delayed language development in children [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the prevalence of permanent and permanent dental caries was 39.73% and 67.72% in students, respectively. The results of a 2015 Kumar study of Indian students showed that 47 % of them had tooth caries [18]. The results of a study by Zhang on Chinese students also showed that the prevalence of dental caries was 40% [19].…”
Section: Discussionmentioning
confidence: 99%